PEMBIAYAAN BERMASALAH DI BANK SYARIAH - Suhaimi Suhaimi; Asnaini Asnaini (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2018)
Financing is a process from the analysis of the feasibility of financing to the realization. Realization of financing is not the last stage of the financing process. After the financing realization, sharia banks need to conduct monitoring and supervision of financing, because in term of financing is not impossible to occur problematic financing due to several reasons. Islamic banks should be able to analyze the causes of problem financing so that it can make an effort to reinvent the quality of the financing.